Production Inventory Model with Disruption Considering Shortage and Time Proportional Demand - Khedlekar, Uttam Kumar; Namdeo, Anubhav (Yugoslav Journal of Operations Research; Vol 28 No 1 (2018), 2017)
The disruption occurs in the system due to labor problem, machines breakdown, strike, political issue and weather disturbance etc. Due to this, the customer delays, or there is delay in receiving the product and they may turn to other supplier/product. This paper presents an economic production model for deteriorating items with production disruption. To extend the time horizon, we consider shortage and inventory plan provided accordingly. Time proportional demand is taken into consideration, and we incorporate the analysis of, or technology itself for item’s preservation to reduced deterioration rate. This research is useful to determine when the production will start and when the inventory gets disrupted. The optimal productionand inventory plan are provided, so that the manufacturer can reduce the loss due to disruption. Finally a graph based simulation study is used to illustrate the proposed model. Keywords: Inventory, disruption, deterioration, preservation cost, shortage.